Clinical and economic results of bilateral subthalamic nucleus stimulation in Parkinson's disease. Issue 4 (16th March 2006) - Fraix, V; Houeto, J-L; Lagrange, C; Le Pen, C; Krystkowiak, P; Guehl, D; Ardouin, C; Welter, M-L; Maurel, F; Defebvre, L; Rougier, A; Benabid, A-L; et al.
Abstract : Background: High frequency stimulation of the subthalamic nucleus (STN) is an alternative but expensive neurosurgical treatment for parkinsonian patients with levodopa induced motor complications. Objective: To assess the safety, clinical effects, quality of life, and economic cost of STN stimulation. Methods: We conducted a prospective multicentre study in 95 consecutive Parkinson's disease (PD) patients receiving bilateral STN stimulation and assessed its effects over 12 months. A double blind randomised motor evaluation was carried out at 3 month follow up, and quality of life, self care ability, and predictive factors of outcome following surgery were assessed. The cost of PD was estimated over 6 months before and after surgery. Results: The Unified Parkinson's Disease Rating Scale (UPDRS) motor score improved by 57% (p<0.0001) and activities of daily living improved by 48% (p<0.0001) at 12 month follow up. Double blind motor scoring improved by 51% at 3 month follow up (p<0.0001). The total PD Quality of Life Questionnaire (PDQL-37) score improved by 28% (p<0.001). The better the preoperative motor score after a levodopa challenge, the better the outcome after STN stimulation. Five patients developed an intracerebral haematoma during electrode implantation with permanent after effects in two. The 6 month costs of PD decreased from €10 087 before surgery to €1673 after surgery (p<0.0001) mainly because of the decrease in medication. These savings allowed a return on the procedure investment, estimated at €36 904 over 2.2 years. Conclusions: STN stimulation has good outcomes with relatively low risk and little cost burden in PD patients with levodopa induced motor complications.